A dual-porosity model for coupled leachate and gas flow to vertical wells in municipal solid waste landfills. Issue 9 (15th May 2019) - Hu, Jie; Ke, Han; Lan, Ji-Wu; Chen, Yun-Min; Meng, Meng
Abstract : The performance of vertical pumping wells in municipal solid waste (MSW) landfills can be effectively enhanced if vacuum pressure is applied to the well. In this study, a dual-porosity model for coupled leachate and gas flow to vertical wells in MSW landfills has been established. The proposed model divides waste into fracture and matrix domains; the leachate and gas in these two domains flow horizontally and vertically into a vertical well together, and mass exchange occurs between them. The hydraulic conductivity of the fracture domain is much higher than that of the matrix domain. The model is solved using the finite-difference method to obtain numerical solutions of the leachate pumping rate Q w and leachate level drawdown S . Numerical simulations indicate that Q w and S decrease with the increasing hydraulic conductivity ratio of the fracture and matrix domains, k i r f / k i r m . As the proportion of the fracture domain in the total domain w f increases, additional large pores are available for leachate flow, and Q w and S gradually increase. Q w and S estimated by the single-porosity model are 1·5–3·0 times as large as those obtained using the dual-porosity model. Q w and S increase with the increasing vacuum pressure applied at the pumping well. A field vacuum well pumping test was carried out at Tianziling landfill to verify the proposed model. When the vacuum pressure at the well increased from 0 kPa to −30 kPa, Q w increased from 33 m 3 /day to 45 m 3 /day at t  = 36 h and S increased from 2·7 m to 5·6 m at a radial distance from the pumping well r  = 10 m. The dual-porosity model performed better than the single-porosity model when simulating the pumping test.